Analisis Konflik Kerja antara Departemen Kitchen dan Service, serta Dampaknya terhadap Produktivitas Kerja di Tom Sushi Solo Paragon Mall - Pinsa Astri Ardian; Muhammad Syihabuddin (Jurnal Inovasi Bisnis Manajemen dan Akuntansi, 2025)
This study aims to analyze work conflicts between the kitchen and service departments and their impact on employee productivity at Tom Sushi Solo Paragon Mall. The research applied a qualitative descriptive method using in-depth interviews, direct observation, and document analysis involving four key informants representing both departments. The findings indicate that conflicts generally stem from miscommunication, unclear task distribution, high workload, and differences in work priorities. These conflicts lead to reduced efficiency, decreased motivation, and communication barriers that hinder coordination and teamwork. The study also finds that conflict management strategies tend to rely on compromising and avoiding approaches, while collaborative strategies are rarely implemented. Therefore, a more structured communication system, regular coordination meetings, and internal mediation are needed to minimize conflict intensity and maintain work effectiveness. The results are expected to provide practical insights for restaurant management in strengthening teamwork, enhancing communication, and improving both service quality and employee productivity.